2005
DOI: 10.1097/01.mao.0000185063.20081.50
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous BDNF Rescues Rat Spiral Ganglion Neurons In Vivo

Abstract: The loss of hair cells resulting in a sensorineural hearing loss (SNHL) also leads to the secondary degeneration of spiral ganglion neurons (SGNs). The effectiveness of cochlear implantation in patients with a profound SNHL relies, in part, upon the survival of SGNs; therefore any therapy that can prevent or halt the loss of these neurons would be of potential clinical benefit. Previous research has shown that intracochlear infusion with neurotrophins can provide trophic support to SGNs in deafened guinea pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 28 publications
7
75
0
Order By: Relevance
“…However, the effects on soma area associated with neurotrophin administration are much greater than the cell size changes elicited with electrical stimulation. In fact, several previous studies in guinea pigs have shown that 4 weeks of intracochlear infusion of BDNF resulted in large increases in SG perikaryal size compared to deafened cochleae and cross-sectional areas that were even significantly larger than in normal controls (Agterberg et al 2008;Glueckert et al 2008;McGuinness and Shepherd 2005;Shepherd et al 2005Shepherd et al , 2008. The mechanism(s) underlying this alteration are unclear, but we agree with the suggestion by ) that it may be related to the high concentrations of exogenous neurotrophin applied in these studies using osmotic pumps.…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizesupporting
confidence: 90%
See 1 more Smart Citation
“…However, the effects on soma area associated with neurotrophin administration are much greater than the cell size changes elicited with electrical stimulation. In fact, several previous studies in guinea pigs have shown that 4 weeks of intracochlear infusion of BDNF resulted in large increases in SG perikaryal size compared to deafened cochleae and cross-sectional areas that were even significantly larger than in normal controls (Agterberg et al 2008;Glueckert et al 2008;McGuinness and Shepherd 2005;Shepherd et al 2005Shepherd et al , 2008. The mechanism(s) underlying this alteration are unclear, but we agree with the suggestion by ) that it may be related to the high concentrations of exogenous neurotrophin applied in these studies using osmotic pumps.…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizesupporting
confidence: 90%
“…Profound deafness has been reported to result in reduction in the size of SG neuron perikarya in many previous studies and in various deaf animal models (Agterberg et al 2008(Agterberg et al , 2009Araki et al 1998;Elverland and Mair 1980;Glueckert et al 2008;Leake et al 1999Leake et al , 2007Leake et al , 2011; Leake and Hradek 1988;McGuinness and Shepherd 2005;Shepherd et al 2005;Wise et al 2005). Presumably, reduction in somatic size reflects reduced metabolic requirements of these neurons due to reduced spike activity after deafness (Hartmann et al 1984;Liberman and Kiang 1978;Shepherd and Javel 1997).…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizementioning
confidence: 96%
“…In that case it would be likely that chronic cochlear electrical stimulation would enhance their survival as has been shown for auditory nerve following deafness (Hartshorn et al, 1991;Leake et al, 1991Leake et al, , 1992Leake et al, , 1995Lousteau, 1987;Mitchell et al, 1997;Miller et al, 2003;Miller & Altschuler, 1995). It may also be the case that neurotrophic factors would also enhance survival, as for auditory nerve following deafness (Altschuler et al, 1999;Malgrange et al, 1999;Marzella and Clark, 1999;McGuinness and Shepherd, 2005;Miller et al, 1997;Miller et al, 1998;Schindler et al, 1995;Shepherd et al, this issue;Staecker et al, 1996;Van de Water et al, 1996) with the combination of neurotrophic factors and chronic electrical stimulation potentially the most effective (Kanzaki et al, 2002;Shepherd et al, 2005, this issue). …”
Section: Discussionmentioning
confidence: 99%
“…The region-specific survival effect on SGNs in the NT treatment group is likely to reflect local differences in the effective concentration of NTs available to the SGNs, and there are a number of factors that may contribute to the finding. Unlike the use of mini-osmotic pumps, whereby relatively high levels of NTs were delivered (for more detail see Ernfors et al [9], Staecker et al [10], Miller et al [11], Wise [12], McGuinness and Shepherd [13], Glueckert et al [14], and Agterberg et al [15]), NTCells produce and release more physiological levels of NTs and therefore physical barriers (e.g., fibrous tissue, or simply the distance between the capsules and the [8,41]. ES may lead to an up-regulation of NT receptors [50][51][52] or increased intracellular trafficking of NT receptors that amplify the neuronal responsiveness to limited amounts of NTs in vivo [53].…”
Section: Effects Of Nt Treatment On Sgn Survivalmentioning
confidence: 99%
“…Administration of neuroprotective agents (e.g., the neurotrophins [NTs], brain derived neurotrophic factor, and NT3) in profoundly deafened cochleae has been shown to prevent SGN loss [9][10][11][12][13][14][15][16]. However, the survival promoting effects were short lived once the NT delivery had ceased [17,18], suggesting that ongoing delivery is required for lasting effects.…”
Section: Introductionmentioning
confidence: 99%